(3eONd Edi GdEbJUGO GdQjGVjs - (3ZQS GdOjf(B, (3eMeOs; (3jGSQs ([(3O(B.(3e(B.]s (3eWHYI GdESQGAs, 2004)
(3Cge GdCOhGJ GdQjGVjI GdeSJNOeI aj GdJMdjd GdEbJUGOj,GdeYGOdGJ hGdOhGd hGdXhGgQ GdEbJUGOjI,GdhVY GdCeKd,GdHQeLI GdNWjI hHYV GdJWHjbGJ GdEbJUGOjI,fXQjI GdeHGQjGJ,eSGFd aj GdEbJUGO GdQjGVjs
Keywords: (3GdGbJUGO GdQjGVjs